Pelatihan Strategi Pembelajaran Berbasis Pengembangan Efikasi Diri untuk Meningkatkan Kemampuan Siswa Bercapaian Rendah: Training of Self-efficacy Enhancement-Based Teaching Strategy to Improve the Ability of Low Achievers - Hartono, Hartono; Anwar, Choril; Nugroho, Kurniawan Yudhi; Maharani, Mega Mulianing; Widiyati, Elok; Abidin, Zaenal (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Since the implementation of the Zoning System for Student Admissions, classes in public schools have become academically heterogeneous. High achievers and low achievers are often in the same classroom. In many cases, these low achievers continue to lag because they are trapped in a vicious cycle of poor performance. Therefore, intervention is needed. One of them is by enhancing their academic self-efficacy through the implementation of a teaching strategy specifically designed to achieve this goal. This community service aims to: 1) improve teachers' understanding of the academic self-efficacy construct and its influence on learning, and 2) assist teachers in developing teaching strategies based on academic self-efficacy enhancement. This community service is divided into three stages of implementation: 1) pre-face-to-face training activities, 2) face-to-face training activities, and 3) post-face-to-face training activities. In the first stage, the community service team coordinates with the partner to prepare the necessary arrangements. In the second stage, the team provided the participants with a one-day training session. Twenty-six English teachers participated. After the self-efficacy construct was presented, participants formulated teaching strategies in groups based on the principles of self-efficacy enhancement. These strategies can then be implemented in their respective classes. The participants positively responded to the training. Follow-up activities, such as research on the strategy's impact, are necessary. Therefore, the lectures and the teachers are expected to maintain cooperation.